سيميائية اللغة في التواصل الثقافي بين اللغة العربية والملايوية Language semiotics in cultural communication between Arabic and Malay - Ali, Asem Shehadeh Saleh (2023)
اللغة هي شيء طبيعي مكتسب لدى الإنسان، وأصبحت مفضلة وقيمة مضافة لمن يتقن ويتحدث بأكثر من لغة واحدة، فمعظم البحوث التي أجريت في مجال اللغة، كان محورها معرفة كيفية اكتساب اللغة وكيفية تطوّرها وممارسة تدريسها على أسس لسانية ونفسية واجتماعية وتربوية، والسيميائية هي الدراسة المنهجية لعمليات الإشارة وصنع المعنى أو هي أي نشاط أو سلوك أو عملية تتضمن إشارات؛ حيث يتم تعريف الإشارة على أنها أي شيء ينقل شيئاً ما، ويُطلق عليه عادةً معنى لمترجم الإشارة، وهي تعد علماً يدرس الدلائل في الحياة الاجتماعية، وقد تكون جزءاً من علم النفس الاجتماعي أو علم النفس العام؛ أي أنها العلم الذي يدرس الأنظمة الرمزية في كل الإشارات الدالة وكيفية هذه الدلالة، وبهذا تنقسم إلى سيميائية التواصل وسيميائية الدلالة. هذه الدراسة تسعى إلى بيان الآثار السيميائية في الجانب الثقافي بين اللغة العربية والملايوية، ومعرفة مدى تأثير الثقافة في هاتين اللغتين، وتحديد نقاط التواصل بينهما. ستتبع الدراسة المنهج الوصفي التحليلي لبيان سيميائية اللغة العربية واللغة الملايوية. وقد توصلت الدراسة إلى نتائج، منها: أن السيميائية لا تحدد فقط مجال التفسير أو التأويل للنص ولا الصورة بل إن أهميتها أكثر من هذا؛ لأنها تقترب إلى مفهومه، وأن اللسانيات دراسة عامة تقوم على بناء نظرية لسانية يمكن تطبيقها على جميع اللغات الإنسانية، وهي تحتوي عن القوى الموجودة في اللغات، واكتشاف تطور السيميائية واللسانيات بعامة في ماليزيا خاصةً، فضلاً عن اللغة الملايوية التي لديها قيمة اللغة نفسها. Abstract Language is acquired by human being, and it has become preferred and additional value for those who master and speak more than one language. Most of the research conducted in the field of language focused on knowledge of how language is acquired, how it develops, and the practice of teaching it on linguistic, psychological, social, and educational bases. Semiotics is the systematic study of sign processes and meaning making. Semiosis is any activity, conduct, or process that involves signs, where a sign is defined as anything that communicates something, usually called a meaning, to the sign's interpreter, a science that studies evidence in social life and may be part of social psychology or general psychology; That is, it is the science that studies symbolic systems in all signifying signs and how this signifies, and thus it is divided into two types; the semiotics of communication and the semiotics of semantics. This study seeks to show the semiotic effects in the cultural aspect between the Arabic and Malay languages, and to find out the extent to which culture influences these two languages, and to identify the points of contact between these two languages. The study will follow the descriptive analytical approach to explain the semiotics of the Arabic and Malay languages. The results of this study including: that the semiotics is not limited only to interpretation of the text or the image, but rather its importance is more than this because it approaches to its concept in an implicated aspect or in an essential aspect, and that linguistics is a general study based on building a linguistic theory that can be applied to all Human languages and contains the powers that exist in languages and the discovery of the development of semiotics and linguistics in general in Malaysia, as well as the Malay language has the value of language itself.